2012
DOI: 10.1039/c2gc16631c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ruthenium catalysed synthesis of γ-valerolactone in alcohols and utilisation of mild solvent-free reaction conditions

Abstract: Levulinic acid and alkyl-levulinates have been hydrogenated using a range of supported catalysts. The different reaction outcomes obtained in alternate solvents have been rationalized and the influence of varying catalyst supports examined. A range of solvent free conditions have been investigated with complete LA conversion obtained at temperatures as low as 25 °C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
212
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(225 citation statements)
references
References 29 publications
12
212
1
Order By: Relevance
“…All samples are basically agglomerates of more or less rounded nanoparticles, with relatively larger size for A and D compared to B and C. Note that B and C are prepared by the calcination of ZrOH after loading RuCl 3 while A and D were prepared by loading RuCl 3 on pre-calcined ZrOH. The results are analogous to the ones we reported elsewhere for WO x /ZrO 2 catalysts, [17] where the calcination of WO x doped ZrOH yielded smaller nanoparticles compared to the calcined, undoped ZrOH. More insight is obtained from a detailed analysis of selected representative high resolution images (see Fig.…”
Section: Scheme 1 Catalytic Hydrogenation Of Levulinic Acid To Variousupporting
confidence: 75%
See 4 more Smart Citations
“…All samples are basically agglomerates of more or less rounded nanoparticles, with relatively larger size for A and D compared to B and C. Note that B and C are prepared by the calcination of ZrOH after loading RuCl 3 while A and D were prepared by loading RuCl 3 on pre-calcined ZrOH. The results are analogous to the ones we reported elsewhere for WO x /ZrO 2 catalysts, [17] where the calcination of WO x doped ZrOH yielded smaller nanoparticles compared to the calcined, undoped ZrOH. More insight is obtained from a detailed analysis of selected representative high resolution images (see Fig.…”
Section: Scheme 1 Catalytic Hydrogenation Of Levulinic Acid To Variousupporting
confidence: 75%
“…We must ensure that we hydrogenate only the keto group, enabling the cyclisation to the lactone product. Previous studies have shown that both the size and the dispersion of the ruthenium sites are crucial, as well as the properties of the support [17,21,32,33]. This is because the hydrogenation of keto group is catalysed by a combined effort of both the ruthenium active site and the support.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations